Local Wisdom-Based Folklor Digital Storytelling through Metacognitive Strategy - Noor Faridha (Universitas Insan Budi Utomo, 2024)
This study seeks to examine the impact of metacognitive strategies on improving students' English as a Foreign Language (EFL) skills in fictional writing. A quasi-experimental approach employing only one group with pre-test and post-tests was utilized to achieve the goal. A total of 30 students from the English Department participated in the research. The findings indicate that employing metacognitive strategies has been demonstrated to be effective in enhancing students' proficiency in writing folklore based on Indonesian stories from the past. Additional empirical investigation is advised to ascertain the impact of the metacognitive method on students' proficiency in a different style of literary composition.